2015
DOI: 10.1007/s10900-015-0060-y
|View full text |Cite
|
Sign up to set email alerts
|

Infant Safe Sleep Interventions, 1990–2015: A Review

Abstract: Sleep-related infant deaths remain a major public health issue. Multiple interventions have been implemented in efforts to increase adherence to safe sleep recommendations. We conducted a systematic review of the international research literature to synthesize research on interventions to reduce the risk of sleep-related deaths and their effectiveness in changing infant sleep practices. We searched PubMed, CINAHL, PsycINFO, and Google Scholar for peer-reviewed articles published between 1990 and 2015 which des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 43 publications
(405 reference statements)
1
36
0
Order By: Relevance
“…In a review of the literature focused on interventions to increase adherence with infant safe sleep recommendations, Ward and Balfour (2015) reported that the majority of studies utilized indirect measures of complianceself-report questionnaires that ask about intent to adhere to or retrospective use of safe sleep recommendations-to evaluate outcomes. For example, Moon et al (2017) conducted a randomized clinical trial in which 1,600 mothers were randomly assigned to one of four groups to evaluate the individual and combined effects of two interventions (nursing quality improvement and mobile health messaging) on adherence with infant safe sleep practices.…”
mentioning
confidence: 99%
“…In a review of the literature focused on interventions to increase adherence with infant safe sleep recommendations, Ward and Balfour (2015) reported that the majority of studies utilized indirect measures of complianceself-report questionnaires that ask about intent to adhere to or retrospective use of safe sleep recommendations-to evaluate outcomes. For example, Moon et al (2017) conducted a randomized clinical trial in which 1,600 mothers were randomly assigned to one of four groups to evaluate the individual and combined effects of two interventions (nursing quality improvement and mobile health messaging) on adherence with infant safe sleep practices.…”
mentioning
confidence: 99%
“…These include lack of consistent education, parental preference, infant comfort, and parents' fear of risk of infant choking. Parents of full-term newborns cited similar barriers including conflicting information, fear of choking, infant comfort, and parental exhaustion as reasons for not following safe sleep practices at home (Salm Ward & Balfour, 2016). Another area of concern was that parents thought the use of a home monitor would decrease the risk of SIDS.…”
Section: Resultsmentioning
confidence: 99%
“…Nursing education initiatives have also been shown to improve nursing compliance with safe sleep for premature infants. In a review of studies in the full-term newborn population with a bundled interventional approach including policy changes, nursing education, and continued yearly competencies for safe sleep, authors showed some degree of success in improving safe sleep compliance (Salm Ward & Balfour, 2016). A statewide safe sleep training program for nurses in Missouri behavioral organization in preterm infants (Sweeney & Gutierrez, 2002).…”
Section: Consistent Education For Parentsmentioning
confidence: 99%
“…Previous reviews of behavioral or non-pharmacological sleep interventions have either focused on underage populations, such as infants [40, 41] or children [42–44]; older people [45, 46]; populations with health problems, such as youth with chronic health conditions [47], children with autism spectrum disorders [48], hospitalized patients [49], oncology patients and family caregivers [50], adults in intensive care units [51]; or people with sleep disorders, such as apnea [5254] or insomnia [55, 56]; or on specific interventions, such as stress reduction [57]. …”
Section: Introductionmentioning
confidence: 99%
“…These reviews included the following types of behavioral sleep interventions: educational interventions (e.g., providing parents information on safe sleep among infants [40] or on positive routines to favor sleep in their child [42, 44]), sleep education [43, 50] or sleep hygiene education [46, 49], cognitive behavioral therapy [43, 50, 55, 56] or cognitive therapy [46], environmental interventions (e.g., reducing environmental noise in aged care facilities [45]), relaxation [49, 51, 55, 56] or massage [51] or aromatherapy [51] or stress reduction [57], and exercise [50] or lifestyle, and dietary interventions [52, 53]. …”
Section: Introductionmentioning
confidence: 99%